Formulation, Evaluation of Physical Properties, Anti-Cholesterol Activity from Ficus carica L. Leaves Extract Tablet - Muhammad Fariez Kurniawan; Mia Audita (Research Center of Inorganic Materials and Coordination Complexes, FMIPA Universitas Sriwijaya, 2021)
Figs knew playing vital roles in reducing cholesterol, strengthening the heart, and controlling respiration. Figs leaves extract with a dose of 50 mg/kg and 100 mg/kg can reduce triglyceride levels and can increase HDL cholesterol levels. This study aims to determine the effect of Ficus carica L. (fig) leaves extract on tablet dosage forms to reducing total cholesterol in rats induced with pork fat feed. Tablets were made by the wet granulation method in three formulas, there are F1 (extract dose 50 mg), F2 (extract dose 100 mg), and F3 (extract dose 150 mg), and compared with simvastatin tablets. The rats used in this study were 40 animals which were divided into 8 groups. Negative control group (induced of pork oil), F1 group, F2 group, F3 group, F4 group (placebo), positive control group (simvastatin 10 mg), base suspending agent group, and normal group.The average weight (mg) of F1 tablets (605.96 ± 9.94%), F2 (611.81 ± 12.33%), and F3 (639.09 ± 4.65%). As for the uniformity of size, all formulas have a diameter of 0.9 ± 0.0 (cm). for the hardness values of F1 (6.54 kg), F2 (5.31 kg), and F3 (5.43 kg). The value of friability F1 (0.8%), F2 (1.38%), and F3 (0.77%). While the disintegration time of F1 (13.31 minutes), F2 (19.48 minutes), and F3 (21.11 minutes). Whereas the dissolution rate (DE45) of each formulation decreased with increasing dose of extract, F1 (69.43%), F2 (64.95%), and F3 (60.04%). Extract contain quercetin as flavonoid, saponin, polyphenol, alkaloid, and tannin. Based on the results of statistical analysis, extract tablets did not differ significantly from simvastatin tablets in reducing total cholesterol levels. Tablet formulation of fig leaves extract with a dose variant has been shown to reduce total cholesterol in the blood between 18.3% until 37.98%.